2007
DOI: 10.1111/j.1651-2227.2007.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening Copenhagen school children at risk of type 2 diabetes mellitus using random capillary blood glucose

Abstract: Our study shows a high prevalence of overweight adolescents in Copenhagen, especially in school areas with low socio-economic standard and in pupils with Turkish, Pakistani and Arab ethnicity. Only three out of the 10 pupils with the highest risk participated. New strategies to reach and motivate risk groups to follow health recommendations and new methods of screening should be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The remaining 12 studies focused on adolescents who were at high-risk for developing prediabetes and T2D. Of these, two examined populations from low-income families (Adams & Lammon, 2007;Herder et al, 2007), three examined adolescents from high-risk ethnic groups (Gomez & Huffman, 2008;Grant et al, 2008;Spurr, Bally, Bullin, & Trinder, 2017), and seven examined adolescents identified as being high-risk based on their anthropometric measures (overweight/obese) (Amiri et al, 2015;Moadab, Kelishadi, Hashemipour, Amini, & Poursafa, 2010;Panamonta, Thamsiri, & Panamonta, 2010;Pearson, Brolos, Herner, Hansen, & Olsen, 2007;Prasad et al, 2016;Shah, Kublaoui, Oden, & White, 2009;Zhu, Zhang, Li, Xie, & Yang, 2013). Because the study designs were heterogeneous and cannot be compared, the results are presented thematically to ensure comprehensive description.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 12 studies focused on adolescents who were at high-risk for developing prediabetes and T2D. Of these, two examined populations from low-income families (Adams & Lammon, 2007;Herder et al, 2007), three examined adolescents from high-risk ethnic groups (Gomez & Huffman, 2008;Grant et al, 2008;Spurr, Bally, Bullin, & Trinder, 2017), and seven examined adolescents identified as being high-risk based on their anthropometric measures (overweight/obese) (Amiri et al, 2015;Moadab, Kelishadi, Hashemipour, Amini, & Poursafa, 2010;Panamonta, Thamsiri, & Panamonta, 2010;Pearson, Brolos, Herner, Hansen, & Olsen, 2007;Prasad et al, 2016;Shah, Kublaoui, Oden, & White, 2009;Zhu, Zhang, Li, Xie, & Yang, 2013). Because the study designs were heterogeneous and cannot be compared, the results are presented thematically to ensure comprehensive description.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies reported measuring overweight and obesity with rates in the participants ranging from 14.64 to 76%. Seven of these studies used inclusion criteria for classifications of overweight and obese (Amiri et al, 2015;Moadab et al, 2010;Panamonta et al, 2010;Pearson et al, 2007;Prasad et al, 2016;Shah et al, 2009;Zhu et al, 2013); however, the procedures for measuring and calculating overweight/obesity were inconsistent across studies. The various guidelines used for overweight/obesity classification included the Center for Disease Control guidelines, adult body mass index (BMI) guidelines, international standards for child overweight and obesity, Chinese criteria (age and sex specific cut-off points to define overweight/obesity as recommended by a working group in China), and World Health Organization (WHO) standards.…”
Section: Risk Factors For Prediabetes and Type 2 Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…There are consequences of this excess weight; a study of Copenhagen schoolchildren found that the higher their BMI in childhood, the greater their risk of coronary heart disease in adulthood (3). Furthermore, type 2 diabetes mellitus, which increases the risk of cardiovascular disease, has also been found in Copenhagen schoolchildren (4).…”
mentioning
confidence: 99%